Host Matters: Medicinal Leech Digestive-Tract Symbionts and Their Pathogenic Potential - Marden, Jeremiah N.; McClure, Emily A.; Beka, Lidia; Graf, Joerg (Frontiers in Microbiology, 2016)
Digestive-tract microbiota exert tremendous influence over host health. Host-symbiont model systems are studied to investigate how symbioses are initiated and maintained, as well as to identify host processes affected by resident microbiota. The medicinal leech, Hirudo verbana, is an excellent model to address such questions owing to a microbiome that is consistently dominanted by two species, Aeromonas veronii and Mucinivorans hirudinis, both of which are cultivable and have sequenced genomes. This review outlines current knowledge about the dynamics of the H. verbana microbiome. We discuss in depth the factors required for A. veronii colonization and proliferation in the leech crop and summarize the current understanding of interactions between A. veronii and its annelid host. Lastly, we discuss leech usage in modern medicine and highlight how leech-therapy associated infections, often attributable to Aeromonas spp., are of growing clinical concern due in part to an increased prevalence of fluoroquinolone resistant strains.